The impact of democratic, permissive and authoritarian parenting styles on adolescent self-confidence: Evidence from senior high school students in Indonesia - Fitrianto, Moh. Shohibul Roziqi; Hakim, Zun Azizul; Marwing, Arman (Utan Kayu Publishing, 2025)
Parenting styles significantly influence adolescent self-confidence, particularly during high school, a critical stage of identity development. This study examines the effects of authoritarian, democratic, and permissive parenting styles on the self-confidence of senior high school students in Blitar Regency, Indonesia. Using a quantitative correlational design, data were collected through questionnaires from 78 students aged 15–17. Descriptive analysis showed that democratic parenting had the highest mean score (M = 44.06, SD = 6.96), while permissive parenting had the lowest (M = 23.28, SD = 5.63). Multiple linear regression analysis indicated that democratic parenting positively influenced self-confidence (B = 0.513, p < 0.05), whereas authoritarian (B = -0.242, p = 0.016) and permissive styles (B = -0.223, p = 0.050) had negative effects. The model explained 35.9% of the variance in self-confidence (Adjusted R² = 0.359). These findings emphasize the importance of democratic parenting, which balances emotional support with structured guidance, in fostering adolescent self-confidence. The study provides practical insights for parents, educators, and policymakers in Indonesia, highlighting the need for parenting programs that promote warmth, open communication, and appropriate boundaries. These strategies can enhance adolescent psychological well-being and contribute to more effective educational and family interventions.